Cover Feature: Interaction of Single Cells with 2D Organic Monolayers: A Scanning Electrochemical Microscopy Study (ChemElectroChem 20/2018). Issue 20 (10th September 2018) - Bartolini, Luca; Malferrari, Marco; Lugli, Francesca; Zerbetto, Francesco; Paolucci, Francesco; Pelicci, Pier Giuseppe; Albonetti, Cristiano; Rapino, Stefania
Abstract : The Cover Feature illustrates that the shape of a living cell is influenced by the organic monolayer where they adhere. Single‐cell scanning electrochemical microscopy and a "learning process" are used to determine the regime of cell‐substrate interaction. More information can be found in the Communication by L. Bartolini et al. onpage 2975 in Issue 20, 2018 (DOI:10.1002/celc.201800731 )